If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(t + 6) + 3t = 4(3t + 4) + -8 Reorder the terms: 9(6 + t) + 3t = 4(3t + 4) + -8 (6 * 9 + t * 9) + 3t = 4(3t + 4) + -8 (54 + 9t) + 3t = 4(3t + 4) + -8 Combine like terms: 9t + 3t = 12t 54 + 12t = 4(3t + 4) + -8 Reorder the terms: 54 + 12t = 4(4 + 3t) + -8 54 + 12t = (4 * 4 + 3t * 4) + -8 54 + 12t = (16 + 12t) + -8 Reorder the terms: 54 + 12t = 16 + -8 + 12t Combine like terms: 16 + -8 = 8 54 + 12t = 8 + 12t Add '-12t' to each side of the equation. 54 + 12t + -12t = 8 + 12t + -12t Combine like terms: 12t + -12t = 0 54 + 0 = 8 + 12t + -12t 54 = 8 + 12t + -12t Combine like terms: 12t + -12t = 0 54 = 8 + 0 54 = 8 Solving 54 = 8 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -(u+5)+5(2u+3)= | | -7u-30=4(u+9) | | 2r^3+16r^2=18 | | 5(1+4a)=105 | | 4X*2-12=16 | | 15/-1/3 | | 28=-2(4+3x)+7(x+4) | | (X-8)14=28 | | 4(2u+2)-12u= | | 4(5x-5)=20(x+1) | | 4(2u+2)-12= | | 5(x+3)=9x+43 | | (-5)(4-5x)=7-3(3x-9) | | 7w+21=-5(w+3) | | -3g-7=-7-2g | | 33-x=26 | | 7x+10=6x+17 | | -(x+3)+6x= | | 23-x=17 | | 9x^2-17=-16 | | -7(1+4x)=217 | | 6x+9=4x+25 | | 8-7j=-6j | | 12+1y+3y=28 | | (2x-1)/3=5x-6/4 | | 2x-9=3x+0 | | 4=-2(4.50+25p) | | -32-8x+6x=12 | | -3(w+1)-4= | | 58=3x+4x+2 | | p=5+2q | | 4=-2(4.50+25) |